The increasing role of the hip extensor musculature with heavier compound lower-body movements and more explosive sport actions - Beardsley, C.; Contreras, B. (Strength and Conditioning Journal, 2014)
Hip extension moments increase to a much greater degree than knee extension moments with increasing loads during the squat, lunge, and deadlift exercises and with increasing running speeds, jump heights, and lateral agility maneuvers. Therefore, hip extension training should be prioritized in athletic conditioning by (a) using hip-dominant exercises in the athlete's program, (b) emphasizing heavier loads during compound lower-body resistance exercises as the athlete matures, and (c) incorporating loads that maximize the hip extension moment during explosive lower-body training.